Preferensi Konsumen dan Kesediaan Membayar pada Jeruk Lokal di Sumatera Utara: Analisis Discrete Choice Experiment - Putra Irwandi; Daffa Ibra Danendra; Surya Sevi Wijayanna Lumban Tobing (Universitas Galuh, 2026)
Local oranges are one of the leading horticultural commodities in North Sumatra and have considerable potential for further development. However, increasing competition from imported fruits requires a deeper understanding of consumer preferences and their willingness to pay (WTP) for the attributes of local oranges. This study aims to analyze consumer preferences and estimate consumers' willingness to pay for local orange attributes in North Sumatra using the Discrete Choice Experiment (DCE) approach. Primary data were collected through a survey of local orange consumers in North Sumatra using a choice set-based questionnaire. The attributes analyzed included fruit freshness, water content, taste, and price. Data were analyzed using the Multinomial Logit (MNL) model. The results indicate that taste is the most influential attribute affecting consumer preferences, followed by fruit freshness. In contrast, the water content attribute has a negative effect on consumer utility, whereas the price attribute has a positive and significant effect on consumers' choice decisions. These findings suggest that consumers in North Sumatra prefer local oranges with better taste and higher freshness and are willing to pay a premium for these desirable attributes. Therefore, improving taste quality and fruit freshness should be prioritized in the development and marketing strategies of local oranges to enhance their competitiveness in the market.